Gut Microbiota Shifting in Irritable Bowel Syndrome: The Mysterious Role of Blastocystis sp. - Olyaiee, Alireza; Sadeghi, Amir; Yadegar, Abbas; Mirsamadi, Elnaz Sadat; Mirjalali, Hamed (Frontiers in Medicine, 2022)
Irritable bowel syndrome (IBS) is a chronic disorder, which its causative agent is not completely clear; however, interaction between microorganisms to each other and to gastrointestinal (GI) epithelial cells play critical role in development of IBS and presenting symptoms. During recent decades, many studies signified the high prevalence of Blastocystis sp., in IBS patients and suggested a probable role of this protist in this disease. Recent studies documented changes in the gut microbiota composition in IBS patients regarding the presence of Blastocystis sp.; it not clear that either disturbance of the gut during GI disorders is a favorable condition for Blastocystis sp., colonization or the presence of this protist may lead to IBS development and symptoms presentation. In this review, we comprehensively gather and discuss scientific findings covering the role of Blastocystis sp., in IBS via gut microbiota shifting.